(untitled) (World Bulletin of Public Health, 2025)
Obligatory precancerous diseases in the oral cavity are pathological conditions noted in epithelial tissues, which increase the probability of cancer development. Such diseases include leukoplakia, erythroplakia, some forms of lichen planus, and others The article describes the clinical manifestations, pathogenesis and diagnostic methods of obligate precancerous diseases in the oral cavity. Also, the probability of these cases turning into cancer and preventive measures are considered. The importance of etiotropic and symptomatic approaches to treatment, as well as the need for regular control, are emphasized. The results of the research are aimed at creating an opportunity to prevent oncological diseases by early detection of pre-cancerous diseases in the oral cavity and taking effective treatment measures against them.